Artropoda Predator Penghuni Ekosistem Persawahan Lebak dan Pasang Surut Sumatera Selatan - Khodijah Khodijah; Siti Herlinda; Chandra Irsan; Yulia Pujiastuti; Rosdah Thalib (Research Center for Suboptimal Lands (PUR-PLSO), Universitas Sriwijaya, 2012)
Khodijah, S. Herlinda, C. Irsan, Y. Pujiastuti, R. Thalib. 2012.Â Predatory Arthropods InhabitingFresh Swamp and Tidal Lowland Ecosystem in South Sumatra. J. Lahan Suboptimal 1(1):57-63Â Research of predatory arthropods inhabiting fresh swamp and tidal land ecosystem in South Sumatra used survey method. The objective of this reasearch was to identify families of the predatory arthropods found in the fresh swamp and tidal land ecosystem in South Sumatra. Survey occured in January up to March 2012. The predatory arthropods were sampled using net and pitfall trapping. The predatory arthropods found were Insecta and Arachnida. Ordo of predatory insects found were Coleoptera, Dermaptera, Diptera, Hemiptera, Orthoptera, Odonata, and Hymenoptera, while predatory spiders found were ordo Araneae. Predatory arthropods inhabiting paddy canopy were almost trapped by net traps, while soil dwelling arthropods were trapped by pitfall traps. The dominant predatory insects found were families of Carabidae and staphylinidae, while dominant family of spiders was Lycosidae. Key species of the predatory artrhopods found from the fresh and tidal land ecosystem were Pheropsophus occipitalis, Paederus fuscipes, Coccinella arcuata, Pardosa pseudoannulata, Oxyopes sp., Pardosa sumatrana, Verania lineata, Broscus sp., and Chelisoches sp.